An Initial Development Of Simple And Low-Cost Approach For Affordable Semi-Automatic Car - Mohamad, Najmiah Radiah; Yusoff, S. A. S.; Salleh, Azahari; Hashim, Nik Mohd Zarifie; Yusop, Norbayah; Misran, Mohamad Harris (IJARET, 2014)
-